A Jauharah Hijab Web Site Design - Eri Mardiani; Nur Rahmansyah; Sari Ningsih; Endah Tri Esthi Handayani; Aditya Nur Rohman; Cintia Marito Sihombing; Ratih Tri Lestari; Trie Widiarti Ningsih; Yusriana Chusna Fadilah (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
In this modern era, Muslimah fashion in Indonesia has become one of the fastest-growing sectors, making many consumers look for Muslimah fashion to follow this fashion trend. Muslim women in Indonesia have various tastes in wearing Muslim clothing. Muslim clothing known as the hijab now has many views with an interesting variety of creativity, so this has caused many Muslim women in various circles in Indonesia to wear the hijab for their daily clothes. This hijab business is a business that has a very small loss potential because the hijab is a product that is not easily damaged and does not spoil. Correct storage and skills in creating new variations and combining clothes and hijab with trendy styles will make the hijab sell well. The target market is not only adult women but various groups, ages, and social statuses because the modern hijab is now more flexible and can be combined with everyday clothes.